2013
DOI: 10.5455/2320-1770.ijrcog20130620
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of programmed labor and traditional management of labor

Abstract: Background: Prolongation of labor leads to dehydration, ketoacidosis, infection, fetal asphyxia. Programmed labor aims at reducing the duration of labor, labor pain and incidence of cesarean section with improved maternal and neonatal outcome. Aims and Objectives: 1)To evaluate the effect of programmed labor on duration of labor. 2)To assess efficacy of analgesics in reducing pain of labor. 3)To find out maternal and neonatal complications. 4)To study impact of programmed labor on LSCS rates. Methods: Prospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…12 There was no statistically significant difference in the Apgar score between the study group and the control group and all the newborns in both groups had satisfactory Apgar scores. Similar findings were observed by Daftary et al and Kshirsagar et al 2,14 In this study, no maternal complications were observed immediately, 24 hours and 1 week after giving PNB. Kshirsagar et al reported drug-related side effects like nausea, vomiting, and drowsiness that subsided after 12 hours, hypertonic contractions (5%).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…12 There was no statistically significant difference in the Apgar score between the study group and the control group and all the newborns in both groups had satisfactory Apgar scores. Similar findings were observed by Daftary et al and Kshirsagar et al 2,14 In this study, no maternal complications were observed immediately, 24 hours and 1 week after giving PNB. Kshirsagar et al reported drug-related side effects like nausea, vomiting, and drowsiness that subsided after 12 hours, hypertonic contractions (5%).…”
Section: Discussionsupporting
confidence: 92%
“…The studies, where the combination of parenteral opioids and antispasmodic was used as labor analgesia, the percentage of instrumental delivery was found to be higher than the present study. 2,3,14 Mousa et al and Fan et al reported that 87.5% and 83.33% patients had normal vaginal delivery, 5%, and 10% had instrumental delivery and 7% and 6.67% had cesarean section respectively. They had used epidural anesthesia as labor analgesia.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation